Faculty of pharmacy showcases “Pharmatopia” at Sulam @ UiTM showcase 2025 - Taridi, Nur Syazwani; Md Hussin, Nur Sabiha (Faculty of Pharmacy, 2025)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam proudly participated in the SULAM@UiTM Showcase 2025, held on 1st July 2025 at Dewan Seroja, UiTM Shah Alam. SULAM, which stands for Service-Learning Malaysia-University for Society, is an initiative developed by the Ministry of Higher Education (MoHE), Malaysia. This program aims to promote experiential education by aligning student activities with community needs, thereby enhancing the overall learning experience for students. SULAM@UiTM Showcase 2025 is a university-level event aimed to recognise the impactful contributions of students and academic staff in implementing high-quality SULAM projects. The showcase also served as a strategic platform to align SULAM implementation across UiTM campuses and to identify top projects to represent UiTM at the national SULAM Innovate competition under the MoHE.